The impacts of learning motivation, emotional engagement and psychological capital on academic performance in a blended learning university course - Liu, Yan; Ma, Shuai; Chen, Yue (Frontiers in Psychology, 2024)
Introduction This study aims to explore the relationships among psychological capital, learning motivation, emotional engagement, and academic performance for college students in a blended learning environment. Method The research consists of two studies: Study 1 primarily focuses on validating, developing, revising, and analyzing the psychometric properties of the scale using factor analysis, while Study 2 employs structural equation modeling (SEM) to test the hypotheses of relationships of included variables and draw conclusions based on 745 data collected in a university in China. Results Findings revealed that intrinsic motivation, extrinsic motivation, emotional engagement, and psychological capital all impact academic performance. Extrinsic learning motivation has significant positive direct effects on intrinsic learning motivation, emotional engagement, and psychological capital. Intrinsic motivation mediates the relationship between extrinsic motivation and academic performance. Discussion In future blended learning practices, it is essential to cultivate students’ intrinsic learning motivation while maintaining a certain level of external learning motivation. It is also crucial to stimulate and maintain students’ emotional engagement, enhance their sense of identity and belonging, and recognize the role of psychological capital in learning to boost students’ confidence, resilience, and positive emotions.